Implementasi Peraturan Pemerintah Nomor 1 Tahun 2011 Tentang Penetapan Dan Alih Fungsi Lahan Pertanian Pangan Berkelanjutan Di Kabupaten Kuantan Singingi - Putri Dwi Octari; Sujianto Sujianto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Increased demand and population growth have resulted in land use competition. Rice fields play a major role in food security because they produce the staple food of rice, which is the most important food crop in Kuantan Singingi Regency. In the last four years, the rice needs of the people of Kuantan Singingi Regency can only be met by ±50% of the local land production. It is feared that in the long term it will become food insecurity. One of the factors feared to affect the instability of food productivity in Kuantan Singingi Regency is the area of food production land or paddy fields. The amount of land area for food production or paddy fields is influenced by the establishment and conversion of land functions that occur. The number of land assignments with land conversion that is not commensurate causes a large enough imbalance. Based on this, this study aims to determine the implementation of Government Regulation No. 1/2011 on the Determination and Transfer of Sustainable Food Agricultural Land in Kuantan Singingi Regency. This research uses a theory based on the variables that influence policy implementation according to Smith's theory, namely idealized policies, target groups, policy implementers, environmental factors. Data were obtained through interviews, observation, and documentation and used data analysis techniques. The results showed that the implementation of the determination and transfer of the function of sustainable food agricultural land still has several obstacles, namely the absence of legal sanctions, lack of communication, customary habits, the ability of the government as an implementor is less than optimal in implementing the rules of determination and transfer of land functions to the people of Kuantan Singingi Regency.